2011
DOI: 10.1063/1.3523647
|View full text |Cite
|
Sign up to set email alerts
|

Electronic excitations induced by hydrogen surface chemical reactions on gold

Abstract: Associated with chemical reactions at surfaces energy may be dissipated exciting surface electronic degrees of freedom. These excitations are detected using metal-insulator-metal (MIM) heterostructures (Ta-TaOx-Au) and the reactions of H with and on a Au surface are probed. A current corresponding to 5×10(-5) electrons per adsorbing H atom and a marked isotope effect are observed under steady-state conditions. Analysis of the current trace when the H atom flux is intermitted suggests that predominantly the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
38
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 55 publications
5
38
1
Order By: Relevance
“…Importantly, this is consistent with the fact that chemicurrent intensities measured during the chemisorption of atoms and molecules scale with the adsorption energy [13][14][15]. Chemicurrents have also been observed during the associative desorption of H 2 on metal surfaces [42,43]. Our finding shows that in these experiments a large amount of e-h pair excitation may take place during the motion of the H atoms on the surface prior to recombination.…”
supporting
confidence: 76%
“…Importantly, this is consistent with the fact that chemicurrent intensities measured during the chemisorption of atoms and molecules scale with the adsorption energy [13][14][15]. Chemicurrents have also been observed during the associative desorption of H 2 on metal surfaces [42,43]. Our finding shows that in these experiments a large amount of e-h pair excitation may take place during the motion of the H atoms on the surface prior to recombination.…”
supporting
confidence: 76%
“…The competition between the e-h pairs and phonon channels governs the relaxation dynamics of the transient hot species, and thus it plays a decisive role in the system reactivity properties. The reason is that it rules the traveled length and relaxation time of a hot atom or molecule on the surface and, consequently, the probability to undergo a recombination reaction with another adsorbate [18][19][20][21][22][23].…”
mentioning
confidence: 99%
“…The competition between the e-h pairs and phonon channels governs the relaxation dynamics of the transient hot species, and thus it plays a decisive role in the system reactivity properties. The reason is that it rules the traveled length and relaxation time of a hot atom or molecule on the surface and, consequently, the probability to undergo a recombination reaction with another adsorbate [18][19][20][21][22][23].Recent ab initio molecular dynamics (AIMD) simulations with electronic friction (AIMDEF) have shown that e-h pair excitations are the dominant relaxation mechanism for hot H atoms on Pd(100) that originate from the dissociative adsorption of H 2 [16]. More particularly, this channel dissipates energy at a five times faster rate than the phonon channel [10].…”
mentioning
confidence: 99%
“…However, a growing number of examples have been found where electronic and nuclear degrees of freedom are strongly coupled in violation of the BOA (2-6). H-atom interactions at metals offer a remarkable opportunity to test non-BOA theories against experiment, since H-adsorptioninduced chemicurrent experiments (7)(8)(9)(10)(11)(12)(13)(14) offer a direct measure of electronic excitation and H-atom inelastic scattering experiments (15) directly probe nuclear motion. In chemicurrent experiments, exothermic H interactions like adsorption and recombination produce hot electrons that pass over a potential barrier to be collected.…”
mentioning
confidence: 99%
“…Hence, the magnitude of the chemicurrent is dependent on both the reaction-induced production of hot electrons and the likelihood of transmission over the barrier. To reduce uncertainties associated with barrier transmission, the ratio of hydrogen-and deuterium-induced chemicurrent is often measured--H-induced chemicurrents are typically two to five times larger than those from D atoms (7,(11)(12)(13). H-atom surface scattering experiments yield H-atom translational energy loss distributions.…”
mentioning
confidence: 99%